2023
DOI: 10.4314/cajeb.v16i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Structure et régénération des peuplements ligneux dans l’Unité Forestière d’Aménagement (UFA) 00-004 dans le Littoral-Cameroun

Abstract: La perte de la biodiversité végétale dans les Unités Forestières d’Aménagements (UFA) est liée aux activités forestières pratiquées dans ce milieu. Ces activités affectent la structure et la capacité de régénération de la forêt. La présente étude vise à analyser la structure et la régénération naturelle de la végétation de l’UFA 00-004 situé dans le Littoral-Cameroun. Les inventaires se sont déroulés dans trois Assiettes Annuelles de Coupes (AAC), dont deux exploitées (AAC 1-1 et AAC 1-2) et une non exploitée … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The fluctuations in these values can be explained by the size of the diameter of the individuals making up each forest and even the density of the wood in each individual. Biomass and carbon sequestration in an ecosystem are influenced by wood density [43,44], Fayolle et al [30]. The quantities of carbon sequestered by the sacred forests in this study are similar to the values found by Tiokeng et al [28] in the sacred forests of Balengou and Bangangté (286.89 tC/ha and 215.67 t C/ha respectively).…”
Section: Quantities Of Carbon and Co2supporting
confidence: 86%
“…The fluctuations in these values can be explained by the size of the diameter of the individuals making up each forest and even the density of the wood in each individual. Biomass and carbon sequestration in an ecosystem are influenced by wood density [43,44], Fayolle et al [30]. The quantities of carbon sequestered by the sacred forests in this study are similar to the values found by Tiokeng et al [28] in the sacred forests of Balengou and Bangangté (286.89 tC/ha and 215.67 t C/ha respectively).…”
Section: Quantities Of Carbon and Co2supporting
confidence: 86%